EPIGENETIC STUDY AS A NEW APPROACH FOR THERAPEUTICS AND BIOMARKER OF ATHEROSCLEROSIS IN COVID-19 - Ferdianti, Fine N; Viradanti, Tersia; Utami, Sinta D (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction : Coronavirus disease 2019 (COVID-19) has affected more than 105 million people globally and resulted in at least 2.3 million deaths. Covid-19 has highlighted the vulnerability of aging populations to emerging diseases. This susceptibility to disease and death is also a major challenge for the development of vaccines and immunotherapeutic agents. Atherosclerosis is one of the main cardiovascular disease, and this disease is one of the most common comorbid diseases affected by Covid-19 and is associated with increased risk of mortality. Biomarker are crucial in decision-making in order to facilitate efficient resource allocation. Recently many researcher develop several biomarker as a new approach in epigenetic area. The discovery of new therapeutic targets as well as biomarkers using epigenetic studies may increase its clinical usefulness.Â Methods: In this narrative review, a search was carried out with the help of several search engines that match the criteria, namely "Epigenetic Studies Based On Cardiovascular Disease Especially In Atherosclerosis".Results: One paper was obtained that supports and fits the criteria, namely the role of miRNA in the formation of atherosclerotic plaques.Conclusion: miR-486-5p can be used as a new therapeutic target and biomarker in atherosclerosis patients, but this requires further research